Defining a research agenda for youth sport specialization in the United States: The AMSSM youth early sport specialization summit - Kliethermes, S. A.; Marshall, S. W.; LaBella, C. R.; Watson, A. M.; Brenner, J. S.; Nagle, K. B.; Jayanthi, N.; Brooks, M. A.; Tenforde, A. S.; Herman, D. C.; DiFiori, J. P.; Beutler, A. I. L. (Clinical Journal of Sport Medicine, 2021)
Sport specialization is becoming increasingly common among youth and adolescent athletes in the United States and many have raised concern about this trend. Although research on sport specialization has grown significantly, numerous pressing questions remain pertaining to short- and long-term effects of specialization on the health and well-being of youth, including the increased risk of overuse injury and burnout. Many current elite athletes did not specialize at an early age. Methodological and study design limitations impact the quality of current literature, and researchers need to prioritize pressing research questions to promote safe and healthy youth sport participation. The American Medical Society for Sports Medicine hosted a Youth Early Sport Specialization Summit in April 2019 with the goal of synthesizing and reviewing current scientific knowledge and developing a research agenda to guide future research in the field based on the identified gaps in knowledge. This statement provides a broad summary of the existing literature, gaps and limitations in current evidence, and identifies key research priorities to help guide researchers conducting research on youth sport specialization. Our goals are to help improve the quality and relevance of research on youth sport specialization and to ultimately assure that opportunities for healthy and safe sport participation continue for all youth.